Research on Live Streaming Sale Strategy for Leather Goods based on Social Media User Behavior Model - Jiangwei HU; Guocai ZHANG (Pige Kexue Yu Gongcheng)
Live streaming sale is an important model for online sale of leather products. How to arouse user interest, stimulate their purchasing desire, and promote their purchasing behavior during live streaming sales is the difficulty of leather product marketing. Based on the social media user behavior model, it was found that the current live streaming sales of leather products generally have problems such as insufficient perception of user consumption expectations, user fatigue caused by homogeneous marketing, lack of deep emotional connection between the transmitting and receiving parties, disconnection between low-priced promotion and purchase conversion, and silence of consumer private domain traffic. It is proposed to use dynamic perception networks to capture user consumption expectations, big data decision-making to anchor user consumption interests, relationship marketing to strengthen user emotional connection, control promotion rhythm to promote purchase conversion, and activate private domain traffic to achieve consumption closed-loop and other live streaming sale strategies.